Integración y cooperación del Derecho privado internacional y europeo según la carta de los derechos fundamentales de la Unión Europea - Liakopoulos, Dimitris (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The time has come, given the relative maturity of the jurisprudence of the Court of Justice of the European Union, regarding the peculiarities linked to the protection of fundamental rights in EU system of civil judicial cooperation to dedicate a detailed investigation and in the field of incidence of EU Charter of Fundamental Rights on EU’s legal system, as well as the specific modalities that affects the elaboration and application of the instruments of civil judicial co-operation.